2010
DOI: 10.1007/s10494-010-9252-9
|View full text |Cite
|
Sign up to set email alerts
|

On the Transition from Deflagration to Detonation in Narrow Tubes

Abstract: The paper is an extension of our recent work on the deflagration-todetonation transition in narrow channels over the transition in narrow circular tubes under more realistic point ignition conditions. The changes from channel to circular tube geometry and from planar to point ignition result in enhancement of the incipient acceleration of the flame and reduction of the predetonation time and distance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Resolution tests also showed the tendency for convergence for the instant of the onset of DDT with increasing resolution. It is noted that convergence tests for DDT is a matter of controversy, 39 with either the suggestion that it is not necessary due to the stochastic nature of the phenomenon, or performing them only for the deflagration stage. However, integrated values of interest, such as saturation velocities or pre-detonation times and distances, should demonstrate convergence to be considered reliable.…”
Section: Discussionmentioning
confidence: 99%
“…Resolution tests also showed the tendency for convergence for the instant of the onset of DDT with increasing resolution. It is noted that convergence tests for DDT is a matter of controversy, 39 with either the suggestion that it is not necessary due to the stochastic nature of the phenomenon, or performing them only for the deflagration stage. However, integrated values of interest, such as saturation velocities or pre-detonation times and distances, should demonstrate convergence to be considered reliable.…”
Section: Discussionmentioning
confidence: 99%
“…Several theoretical and numerical studies predict strong acceleration of flame in small channels. The acceleration rate is enhanced as the tube diameter decreases [1,2,6,14]. Wu et al [4] further experimentally confirmed that deflagration-to-detonation transition (DDT) can occur in tubes with diameters as small as 0.5 mm for stoichiometric ethylene/oxygen mixtures initially at atmospheric pressure.…”
Section: Introductionmentioning
confidence: 98%
“…The computational method adopted and resolution tests are discussed in [15,16]. The parameters employed are specified as follows: (d = l th ) andd = 0.5 (d = 10l th ) at n = 2.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…Then we considered a 1D friction-free version of the problem (1)-(13) with the original reaction rateŴ (7) replaced byŴ = 2Ŵ (16) to ensure the overall mass flux through the flameρ(D −û) to be proportional to , at least for sufficiently lowD. For thick flames (d = l th ) the developing level of folding ( Figure 3) appears to be insufficient for triggering the transition (Figure 2).…”
Section: Numerical Simulationsmentioning
confidence: 99%